The content analysis of theses in the field of health education in Tehran University of Medical Sciences, Tarbiat Modares University and Iran University of Medical Sciences during 1970-2010 - H Rezakhani Moghadam; D Shojaeizadeh; A Nabiolahi; S Moez (Tehran University of Medical Sciences, 2011)
Background and Aim: Theses are considered as one of the sources for research in the field of education. The aim of this study was to determine the popular topics during 1349-1389 (1970-2010) and to examine the amount of educational interference and the type of such interference in different theses. Materials and Methods: This research study was done using the descriptive-analytic method and employing the content analysis technique. The choice of topics was based on the categories derived from the Medical Headings of the American National Library. All related theses (336 in this field) were reviewed and the data were analyzed by SPSS software. Results: In this review, most finished theses belonged to Tehran University of Medical Sciences (62.5%), Tarbiat Modares University (25.3%), and Iran University of Medical Sciences (12.2%). MSc theses were mainly about diseases (23.8%) however, doctoral dissertations were mostly about the prevention of diseases(26.2%). Conclusion: Although in the recent decade, there has been an increase in new topics and educational interference in theses, some important issues like the training of patients are still neglected. It seems that some strategies like preparing a suitable information bank of thesis in the field of health education can be a good guide for selecting new topics and ignoring old ones.